IMPLEMENTASI MANAJEMEN REKAM MEDIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Fahmi Hakam (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2019)
The medical record service management system and good health information in the hospital will be able to create good order and quality of medical record services, so that patients get fast, equitable and orderly services. Based on the observations that have been made, that the medical record management activities in PKU Muhammadiyah Yogyakarta have been going quite, but there are some obstacles related to the process of recording and managing data, as well as other technical matters relating to the provision of medical record files. Is a type of descriptive research with a qualitative approach. From the results of the study, it was found that the forms used in PKU Muhammadiyah Yogyakarta Hospital used paper forms. The medical record forms used in PKU Muhammadiyah Yogyakarta Hospital for generally include polyclinic sheets, emergency sheets, inpatient sheets, medical resumes, doctor's notes, and notes on drug administration. Assembling or compiling medical record files at PKU Muhamadiyah Hospital has been running well and in accordance with applicable regulations. Coding and indexing in PKU Muhammadiyah Hospital in Yogyakarta is not in accordance with the theory because there is no coding for drugs, devices and radiology.